Project method in the teaching of oratory - Cárdenas-Valverde, Elí; Cárdenas, Juan; Flores-Poma, Irina; Quincho-Apumayta, Raúl; Inga-Choque, Vilma; Salazar, Wilfredo (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
The present investigation entitled "Project method in the teaching of oratory" begins with the objective of knowing the degree of influence of the project method in the teaching of oratory to students in the sixth grade of primary school. The study was of a technological-applied type. The methods were used: Analytical-synthetic, which served to base and formulate the research problem. Descriptive method, to explain and develop the theoretical framework. Experimental method, to contrast the reactions between cause and effect in experimentation. Statistical method, to analyze and interpret the results obtained. After applying the experiment, it was obtained that Tc = 17.32 and t0.05 = 9.28, the following relationship is obtained: 9.28 < 17.32, after the statistical analysis submitted, the application of the project method is concluded. a high degree of influence in the teaching of oratory to the students of the sixth grade of primary school of the State School No 30214 of Hualahoyo-Huancayo, also in the mentioned educational center the students overcame difficulties when expressing themselves before an auditorium.